Keeping Distance from Practical Politics: A Critical Analysis of the Muhammadiyah Political Movement from the Catholic Perspective - Yoachim Agus Tridiatno (Politika: Jurnal Ilmu Politik, 2021)
The Muhammadiyah's stance that tends to keep distance from practical politics in line with the ideals of the founder are dynamic and crucial. The tense was very strong between those willing to be faithful to the mission and those wishing to indulge into practical politics. During this period, the elites maneuvered the political moves numerous times until its centennial years. These experiences act as lessons learned from other organizations in Indonesia. The research aims to determine the critical reflection on the political moves of Muhammadiyah from the Catholic perspective. It uses the Catholic Social Teachings as a reflective tool to determine alternative insights on Muhammadiyah.